2017
DOI: 10.1002/jcb.25785
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Activation as a Protective Feedback to Limit Cell Death in High Glucose‐Exposed Cardiomyocytes

Abstract: Hyperglycemia leads to excess reactive oxygen species (ROS) generation, which causes many diabetic complications, such as cardiomyopathy. Nuclear factor erythroid 2-related factor 2 (Nrf2), a redox-sensing transcription factor, can up-regulate its downstream antioxidant gene expressions in response to oxidative stress. However, the regulatory signal pathway in which high glucose (HG) induces Nrf2 activation is still unclear. Our results demonstrated that HG (33 mM) can indeed stimulate Nrf2 protein expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…We demonstrated that High glucose‐induced ROS accumulation will induce Nrf2 activation. However, when knock down Nrf2 will cause cell apoptosis . On the other hand, previous studies indicated that antioxidant herbal products may exert an antisenescent effect process via activating the Nrf2 pathway .…”
Section: Discussionmentioning
confidence: 96%
“…We demonstrated that High glucose‐induced ROS accumulation will induce Nrf2 activation. However, when knock down Nrf2 will cause cell apoptosis . On the other hand, previous studies indicated that antioxidant herbal products may exert an antisenescent effect process via activating the Nrf2 pathway .…”
Section: Discussionmentioning
confidence: 96%
“…Phase II antioxidant enzymes include heme oxygenase-1 (HO-1), NAD(P)H quinone oxidoreductase-1 (NQO-1), and γ-glutamylcysteine synthetase heavy subunit (γ- GCS). Nrf2-mediated antioxidant enzymes were reported to be promising therapeutic targets for limiting oxidative stress and promoting cardioprotection ( Tsai et al, 2017 ). Accordingly, discerning how to promote the translocation of Nrf2 and subsequently increase these antioxidant enzymes has become a promising approach in the treatment of DCM.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is similar to our previous study. In either high glucose‐induced cardiac cell death or H 2 O 2 ‐induced dermal fibroblast cell damage models, this stress eventually leads to ROS formation and Nrf2 activation 26,43,44 . Interestingly, treatment with F‐FEJS further enhanced antioxidant responses to protect dermal cells from UVB‐ or H 2 O 2 ‐induced damage (Figure 6).…”
Section: Discussionmentioning
confidence: 99%